Kinerja Keuangan dan Covid-19: Analisis Uji Beda pada Perusahaan Sektor Keuangan - Ni Luh Putu Anom Pancawati (Sekolah Tinggi Ilmu Ekonomi AMM, 2021)
This study aims to compare the financial performance of the financial sector, namely the sub-sector of finance companies listed on the Indonesia Stock Exchange (IDX) before and during the Covid-19 pandemic. The 2019 financial report describes financial conditions before the Covid-19 pandemic and the 2020 financial report presents financial conditions during the COVID-19 pandemic. The method used in this research is descriptive quantitative. The study was conducted on 16 sub-sectors of finance companies listed on the Indonesia Stock Exchange (IDX). Financial performance is assessed using liquidity ratios through the current ratio and net working capital to total assets, profitability ratios with ROA and ROE, activity ratios using fixed asset turn over, and total asset turn over and leverage ratios calculated through debt to total assets ratio and debt to total equity ratios. The results of this study indicate that the covid-19 pandemic has not yet had an impact on financial sector companies in the financing sub-sector in terms of liquidity ratios, but different results are shown in profitability, activity, and leverage ratios, that the covid-19 pandemic has an impact on financial sector companies, especially in the sub-sector finance company.